Investigation of sand mixture interlayer reducing the thermal constraint strain in asphalt concrete overlay. (20th May 2018) - Sun, Zhiqi; Xu, Yongli; Tan, Yiqiu; Zhang, Lei; Xu, Huining; Meng, Anxin
Highlights: Reduce significantly the constraint-strain of the asphalt concrete overlay. Quantify the constraint-strain of composite structure with sand mixt interlayer. Calculate the restraint coefficient k only with strain response. Calculate the resistance coefficient Cx and thermal stress on the overlay with temperature. Abstract: Semi-rigid base material is widely used because of its lower costs, yet the issue of the incompatibility of cement materials and asphalt materials in the semi-rigid-base asphalt pavement is particularly significant in cold regions. This study examined and quantified the benefits of adding sand mixture interlayer to the semi-rigid base of the asphalt pavement to reduce the thermal-constraint strain of the asphalt concrete overlay with thermal loading. For the two-layer system, the restraint coefficient of the layer structure and interlaminar shear coefficient were calculated on the principles of thermoelasticity theory. For the three-layer structure with sand-mixture interlayer, constraint strains in the interface were determined on pairwise comparison. Results indicate a significant reduction in the constraint-strain of the asphalt concrete overlay and base layer of the three-layer structure. And the constraint-strains of the asphalt concrete overlay of the three-layer structure are nearly identical to samples of the two-layer system with asphalt-treated base. The essential parameters obtained during the calculation are used as the verification calculation of pavement structure design in cold regions.